Endosomal Trafficking Bypassed by the RAB5B‐CD109 Interplay Promotes Axonogenesis in KRAS‐Mutant Pancreatic Cancer - Dingwen Zhang; Yuming Luo; Yan Lin; Zhou Fang; Hanhao Zheng; Mingjie An; Qingyu Xie; Zhuo Wu; Chao Yu; Jiabin Yang; Min Yu; Changhao Chen; et al. (Advanced Science)
Abstract Perineural invasion (PNI) represents a unique biological feature associated with poor prognosis in pancreatic ductal adenocarcinoma (PDAC), especially in the presence of KRAS mutations. Extracellular vesicle (EV)‐packaged circular RNAs (circRNAs) function as essential mediators of tumor microenvironment communication, triggering PDAC cell invasion and distant metastasis. However, the regulatory mechanisms of EV‐packaged circRNAs in the PNI of KRAS‐mutant PDAC have not yet been elucidated. Herein, a KRASG12D mutation‐responsive EV‐packaged circRNA, circPNIT, which positively correlated with PNI in PDAC patients is identified. Functionally, KRASG12D PDAC‐derived EV‐packaged circPNIT promoted axonogenesis and PNI both in vitro and in vivo. Mechanistically, the circPNIT‐mediated Rab5B‐CD109 interplay bypassed traditional endosomal trafficking to anchor Rab5B to the lipid rafts of multivesicular bodies and packaged circPNIT into CD109+ EVs. Subsequently, CD109+ EVs delivered circPNIT to neurons by binding to TRPV1 and facilitating DSCAML1 transcription‐induced axonogenesis, which in turn enhanced the PNI by activating the GFRα1/RET pathway. Importantly, circPNIT‐loaded CD109+ EVs are established to dramatically promote PNI in a KRASG12D/+ Trp53R172H/+ Pdx‐1‐Cre mouse model. Collectively, the findings highlight the mechanism underlying how EV‐packaged circRNAs mediate the PNI of KRAS‐mutant PDAC cells through the Rab5B endosomal bypass, identifying circPNIT as an effective target for the treatment of neuro‐metastatic PDAC.